2017
DOI: 10.5539/sar.v6n4p74
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Farm Yard Manure on Soil Properties and Crop Growth in an Agroforestry System in the Himalaya

Abstract: Many parts of South Asia are facing agricultural land degradation and reduced productivity while the population continues to grow and demand for food is ever-increasing. This paper presents the results of research specifically focused on application of biochar and Farm Yard Manure (FYM) at 5t/ha and 20t/ha, respectively as an amendment on degraded soil in a coffee agroforestry system of the mid-hills in the Nepal Himalaya. The study showed that there were significant (P<0.05) positive effects on soil chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Similarly, biochar from peanut hulls also decreased the leaching of ammonium and nitrate by 14 and 34%, respectively, (Yao et al, 2012). Several field investigations showed that biochar application to agricultural soil considerably decreased the leaching of N, NO 3 − , K, P, Mg, Na, and Ca from soil (Major et al, 2012;Agegnehu et al, 2015;Kammann et al, 2015;Gautam et al, 2017).…”
Section: Nutrient Offering and Retentionmentioning
confidence: 92%
“…Similarly, biochar from peanut hulls also decreased the leaching of ammonium and nitrate by 14 and 34%, respectively, (Yao et al, 2012). Several field investigations showed that biochar application to agricultural soil considerably decreased the leaching of N, NO 3 − , K, P, Mg, Na, and Ca from soil (Major et al, 2012;Agegnehu et al, 2015;Kammann et al, 2015;Gautam et al, 2017).…”
Section: Nutrient Offering and Retentionmentioning
confidence: 92%
“…For instance, in tropical acid soil, soil exchangeable K increased using 5 t ha −1 chicken litter biochar [60]. In a study with Nepalese silty loam soil, Gautam et al [61] reported that biochar contained a high amount of ash, which is responsible for increased exchangeable K, which stimulates for quick discharge of mineral nutrients to the soil [62] along with restraining the loss of K leaching [63].…”
Section: Biochar and Lime Treatment Affects Soil Propertiesmentioning
confidence: 99%
“…Also, VC promotes growth and productivity of wheat (Suthar, 2006 andIbrahim et al, 2015), while VC with BC provides pathogen suppression to plants and increase crop productivity (Shoaf, 2014). Moreover, 5 tons BC with 20 tons FYM/ha (Gautam et al, 2017) or 2.5-5.0% BC+ compost with or without the mineral fertilizer (Schulzand Glaser (2012) provide beneficial effects on plant growth, plant height, crop yield and soil chemical properties.…”
Section: Introductionmentioning
confidence: 99%